Turbidite Reservoir Main Control and Quality - Herman Darman (Berita Sedimentologi, 1997)
Turbidite sandstone can form important reservoir rocks. Some giant oil fields with recognized ultimate recoveries larger than 500 million barrels have been found in turbidite deposits. Some major reservoir units in the North Sea Basin are interpreted as multiple stacked submarine lobes with little evidence of channeling. Other giant turbidite reservoirs were also found in the US and other fields in the world.